Examining the Translation and the Interpretation of ᾱμπɛλος (ampelos) and κλῆμᾱ (klema) as bobe and ban/mman in the Asante-Twi Bible. - Anthony Yaw Badu (Journal of Mother-Tongue Biblical Hermeneutics and Theology, 2021)
Jesus used the vine in the last of his “I AM” predictions in the gospel of John. In this discourse, Jesus used the vine which was familiar to his audience for better understanding and appreciation of God’s word. Great work has been done on the analogy of the vine by scholars and theologians however, little work has been done on the translation of the Greek words, ᾱμπɛλος (ampelos) and κλῆμᾱ (klema) as used in the Asante-Twi Bible. Using the mother-tongue biblical hermeneutics methodology, this article examines the translation and interpretation of ᾱμπɛλος and κλῆμᾱ in the Asante-Twi Bible in comparison with five Ghanaian mothertongue Bibles namely, the Akuapem-Twi Bible, the Fante Bible, and the Ga, Ewe and the Frafra Bibles. The findings show that translators used varied approaches to render ᾱμπɛλος and κλῆμᾱ to suit the understanding of the indigenes. Some translators used transliteration or literal approach, others coined their own words having consulted the indigenes about better terminologies that will suit their understanding of some difficult texts. This article makes a contribution to the need to re-translate and re-interpret the words bobe and ban particularly in the AsanteTwi Bible to avoid speculation.